2019
DOI: 10.1108/ilt-07-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reciprocating and unidirectional sliding motion on the friction and wear of phenolic resin based composite

Abstract: Purpose The purpose of this paper is to investigate the effect of reciprocating and unidirectional sliding motions on friction and wear of phenolic resin-based composite. Design/methodology/approach The phenolic resin-based composite was fabricated by hot press molding, and then the tribological properties were tested on a CSM tribometer with two types of friction motion modes – reciprocating friction and unidirectional friction. Findings The results showed that the composite exhibited low friction coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In practical applications, combined effects of reciprocating and rotating motion are important. Previous studies [ 20 , 21 ] have shown that in the case of rotating motion, friction and wear are seemed to be higher than that of reciprocating motion, and different results are also noted in few cases. However, no clear correlations have been found among combined motion, friction, and wear.…”
Section: Introductionmentioning
confidence: 95%
“…In practical applications, combined effects of reciprocating and rotating motion are important. Previous studies [ 20 , 21 ] have shown that in the case of rotating motion, friction and wear are seemed to be higher than that of reciprocating motion, and different results are also noted in few cases. However, no clear correlations have been found among combined motion, friction, and wear.…”
Section: Introductionmentioning
confidence: 95%
“…Apart from these separate investigations conducted on unidirectional and reciprocating wear, few studies pertaining to a comparison of the two modes can be identified in the literature (Marui and Endo, 2001; Cai et al , 2019). Reddy et al (1995) also investigated the dry wear behavior of Al–Si alloy pins sliding against steel, in both reciprocating and continuous sliding modes and reported that the wear and seizure resistance are highly dependent on the mode of sliding, as well as the reciprocating speed.…”
Section: Introductionmentioning
confidence: 99%
“…Research directions for reciprocating moving parts mainly include friction, wear, lubrication, sealing, and numerical simulation [7][8][9]. Azzi et al found that high friction and low sealing performance due to incorrect sealing material or geometry selection, improper surface texture, incompatible lubricants, or other frictional factors [10].…”
Section: Introductionmentioning
confidence: 99%